Ketamakan dalam Film "Parasite" - Rio Febriannur Rachman (Jurnal Spektrum Komunikasi, 2020)
This article discusses the moral message associated with greed in the Parasite movie. This South Korean-language artwork was chosen because it is the best film in the world by the Academy Awards or Oscar 2020. In 2019, this Bong Joon-Ho's work won Palme d'Or in the 72nd Cannes Film Festival. At the same time, he received an appreciation of eight minutes of a standing ovation from the audience. In January 2020, the movie which originally called Gisaengchung won Best Foreign Language Film at the Golden Globe Awards and Cast in a Motion Picture at the Screen Actors Guild Award. Not only those things, but the movie's track record is also even more interesting because it won the Best Film Not in the English Language in the British Academy of Film and Television Arts 2020, along with a series of awards at other international events. A number of articles discuss the aspects of social inequality shown in this movie. In fact, as a work of art, moral messages in a cinematic product can be diverse and can be examined from a variety of perspectives. This research relies on representation theory that refers to the concept of greed in Islamic and Christian perspectives, as stated in the interpretation of the Holy Qur'an and the Bible. The method used is qualitative with a visual analysis approach in the scope of the site of the image itself. The result of this study, greed depicted in the attitude of one poor family who has a major role in the Parasite.